Bridging the soft skills gap how to teach the missing basics to the new hybrid workforce - Tulgan, Bruce (Hoboken, New Jersey John Wiley & Sons, Inc., 2023)
Soft skills are more important than ever, in the new hybrid workplace, where we all must communicate, cooperate, and collaborate with an ever-wider range of people --- whether remotely or in person. At the same time, there is a growing soft-skills gap throughout the workforce, and not just among the new young workforce, but also among people of all ages. In this second edition of Bridging the Soft Skills Gap, Tulgan recognizes the three key behaviors needed to find success in a workforce of non-conformists. The old-fashioned soft skills needed by our newest and youngest workers have been tracked by Tulgan since 1993, and now in a post-pandemic world of remote work, these skills have an even greater impact on the success of an organization. With 25% more content, Tulgan provides a research-based approach to close the soft skills gap among the newest generation of workers"--
Includes index.
Keywords: Business etiquette; Personnel management; Soft skills; Generation Y -- Employment